The social epidemiology of sexually transmitted diseases among adolescents and young adults in Transkei - Mbananga, Nolwazi Daphne (University of the Free State, 1993)
Respondents (patients) between the ages 15 years and 30 years (N=146) from each selected health clinic of the ten selected districts in Transkei were interviewed using a structred interview schedule. The respondents interviewed were patients who visited health centres and who were diagnosed to be suffering from STDs. The interviews were conducted to obtain information on the influences of geographic, demographic/biographic, socio-cultural and socio-economic factors in the transmission, treatment, prevention and control of STDs. The study was undertaken to provide information for planning STD preventive strategies and to argue why there should be a change in the management of STDs to community-based control measures. Most patients suffered from gonorrhoea and gonoccal urethitis more than any of other STDs. Some patients reported that they had STDs before, whle others did not know. Some patients knew that STDs were infectious and that one contracts them through sexual contacts with infected persons. The most popular source of information on STDs was Radio Transkei Broadcasting Corporation. Pamphlets and other sources of information seem not to be popular. Nurses played limited role as source of information. Most patients did not use condoms during their sexual activities and some of the patints reported to have had sexual intercourse during their illness without condoms. Fourty seven percent of the patients did not like condoms and associated them with people who are HIV positive or had AIDS. Some patients reported that they have heard about condoms, however condoms were not available in their areas. Some patients reported that there were no clinics near their residential areas. Patients reported that even where there were clinics nearer the one they had attended, there was no transport to such clinics. Distances to these clinics were long to be walked. A significant number of patients reported that they consulted traditional healers for their STD problems, because they associated their STD with witchcraft while others did so and when they did not get help from westernised health institutions. It was found that patients visit health centres with some expectations that are related to choice of treatment. Injection appeared to be preferred more than other forms of treatment. Patients did not see AIDS as a greater killer than STDs. Fifty percent of all patients reported that the youth of their areas have promiscuous behaviour and need more information on STDs. Some patients reported that they were ashamed of their STD problems and did not want tot tell other people, even their sexual partners. Patients wanted preventive strategies such as campaigns on prevention of STDs, but did not know how these could be conducted. On whether they found it important to have a sexual contact on the first date of a relationship a significant percentage said yes, while some said no. It would appear that most patients involved themselves in sexual contact with people whose sexual history they did not know. It was deduced that sexual behaviours of this nature were associated with a high risk of transmission of STDs. Most patients did not know what further research could be done on the question of STDs. The few thought that further research should be directed on causes and better methods and strategies of preventing STDs. The study revealed that there is a link between STDs and geographic, demographic / biographic, socio-cultural and socio-economic factors.
Dissertation (M.A. (Sociology))--University of the Free State, 1993
Keywords: Sexually transmitted diseases -- South Africa -- Transkei; Youth, Black -- Health and hygiene -- South Africa -- Transkei